Comprehensive health assessment and five‐yr follow‐up of allogeneic islet transplant recipients. (26th October 2013) - Radosevich, D. M.; Jevne, R.; Bellin, M.; Kandaswamy, R.; Sutherland, D. E. R.; Hering, B. J.
Abstract In patients with type 1 diabetes mellitus (T1DM) complicated by severe hypoglycemic episodes, fear of hypoglycemia can significantly impact daily life. We evaluated whether restoration of glycemic awareness and prevention of hypoglycemia by islet allotransplant could reduce fear and improve health status. We conducted a comprehensive evaluation of patient‐based outcomes in 48 T1DM subjects screened for allogeneic islet transplant alone (ITA) and 27 subjects who received an ITA. A battery of generic health status and diabetes‐specific measures were used to assess ITA at evaluation, six months, and then annually after ITA. Allogeneic islet transplant was associated with a reduction in behaviors adopted in avoiding hypoglycemia (p Value < 0.001) and attenuation in concerns about hypoglycemic episodes (p Value < 0.001). Changes in hypoglycemia fear tracked most closely with insulin use. While there was a trend toward global improvement in health as measured by the EQ‐5D (p Value = 0.002) and in depression symptoms as measured by the Beck (p Value = 0.003), physical health remained unchanged following ITA. Our findings support the socioemotional benefits of ITA during the five years after ITA, which to some extent remains dependent on preservation of islet graft function.